Persuation of Teacher Communication in Preventing the Danger of Drug Abuse on High School Students - Abrar Adhani; Akhyar Anshori (Budapest International Research and Critics University, 2018)
The teacher is one part that has an important role in building the character and mentality of students. High school students are part of the human growth phase in adolescence. Teenagers are part of the leadership baton. At a young age this is also targeted for criminals, including drug traffickers, because adolescence is identical to the age of self-discovery. The methodology carried out in this study with the research design combination of qualitative and quantitative approaches with dominant-less dominant design model. The methodology carried out in this study is divided into 2 parts, the first through the survey methodology and the second through in-depth discussion to obtain results related to the study Drug prevention communication planning for high school students. The results of this study indicate that high school students in Medan City have received information regarding abuse of drug use. Drug abuse can cause physical or psychological dependence. Knowledge that is owned by high school students in Medan City should be followed up by carrying out positive activities. School is a part of the community that determines student attitudes. Activities in school activities must always be in sync with existing development conditions. Schools are not just a learning medium, but schools must play an active role in raising awareness for their students.